Influência da periodontite apical no perfil hematológico de ratos Wistar portadores de insuficiência renal aguda - Costa, Taís Gonçalves [UNESP] (2018)
The objective of this study was to verify the influence of apical periodontitis (AP) on the hematological profile of rats with acute renal failure (ARF). Thirty two rats were divided into four groups (n = 8): Group C - control rats; AP group - rats with apical periodontitis; Group IRA - rats with acute kidney injury; IRA + AP group - rats with acute kidney injury and apical periodontitis. IRA was induced by daily application of Gentamicin (100mg/kg/day) for 8 days intraperitoneally. The AP was induced by means of pulp exposure of the first and second upper and lower right molars and was confirmed radiographically after 15 days. After this period, hematological tissue was collected by means of a cardiac puncture for the analysis of the 13 hemogram parameters (Hemacic, Globular Volume, Hemoglobin, MCV, MCHC, Leukocytes, Neutrophils, Lymphocytes, Monocytes, Eosinophils, Basophils and Total Plasma Protein). The data were tabulated and subjected to statistical analysis (p<0.05). The radiographic analysis was performed through bone resorption along with the exposure of the teeth submitted to the pulp exposure. The increase was significant in leukocytes, lymphocytes and neutrophils, (p<0.05), in the ARF and ARF + AP groups in relation to the control group. In addition, the red series in the IRA and IRA + AP groups. The MCV significantly reduced (p<0.05), mainly in the ARF + AP group. A study was performed of multiple foci of apical periodontitis when associated with ARI, leading to changes in parameters in the blood profile that cause disturbances in the metabolism. Clinical relevance: the presence of endodontic infections can interfere with the blood profile, altering systemic health